Influence of kinetic and thermodynamic promoters on post-combustion carbon dioxide capture through gas hydrate crystallization - Kumar, A.; Bhattacharjee, G.; Barmecha, V.; Diwan, S.; Kushwaha, O. S. (Journal of environmental chemical engineering, 2016)
In the present work, we report enhanced kinetics of hydrate formation in the presence of kinetic and thermodynamic promoters, SDS (sodium dodecyl sulphate) and THF (tetrahydrofuran) respectively. Hydrate formation was carried out in a fixed bed reactor for post-combustion capture of CO2. Silica sand was used as a fixed bed medium to capture CO2 from a CO2/N2/SO2 (17.7 mol% CO2, 1.05 mol% SO2 and balance N2) gas mixture by hydrate crystallisation. Experiments were performed at a constant temperature (273.65 K) and at different pressures (9.5 and 2.45 MPa) in batch mode. It was found that the addition of SDS enhances the rate and gas uptake of gas hydrate formation. A higher gas consumption was achieved by using 5.56 mol% THF compared to 1.0 and 3.0 mol% THF.